Quality of life in persons with lower limb amputations - Modi, Twinkle K.; Mukkamala, Neha L.; Parmar, Lata D. (International Journal Of Community Medicine And Public Health, 2023)
Background: Large number of individuals live with various disabilities in India. Amputation is a major disability which causes irreversible changes and drastically alters everyday functioning. Quality of Life (QOL) in persons with lower limb amputations has been found to be affected. This study aimed to assess the QOL in persons with lower limb amputations using SF-36 via telephone. Methods: This was an observational study. Individuals with lower limb amputations who were enrolled in an orthotic and prosthetic clinic in Vadodara, Gujarat, were interviewed on the telephone to assess their QOL. Individuals with lower limb amputations, 18 years and above and both genders were included and those with impaired vision, hearing, cognition and upper limb amputations were excluded. QOL was assessed using SF-36 questionnaire on the telephone. Results: Total 140 individuals: 119 males, 21 females. 123 had unilateral and 17 had bilateral amputation. There was a significant difference found between unilateral and bilateral amputations in the Energy/Fatigue component of QOL (p=0.017) and between males and females in the Physical Functioning and General Health component of QOL (p=0.001) and (p=0.038) respectively. No significant difference was found in the QOL based on the levels of amputation in individuals with unilateral and bilateral amputation. Conclusions: Physical Functioning and the General Health components of QOL were better in males as compared to females. Individuals with bilateral amputations had more energy compared to individuals with unilateral amputations and hence had a better QOL.